Penggunaan Model Pembelajaran Index Card Match untuk Meningkatkan Keaktifan Belajar IPAS Peserta Didik Kelas V Sekolah Dasar - Uri Ashe Shanti; Sukarno Sukarno (Didaktika Dwija Indria, 2025)
This research aims to enhance students’ learning activeness by applying the Index Card Match (ICM) learning model in Natural and Social Science subjects. This study used a classroom action research design conducted over two cycles, with each cycle consisting of two meetings. The participants were 28 fifth-grade students at Soropadan Elementary School during the 2024/2025 academic year. Data were collected through observation, documentation, interviews, and tests. The research process included four stages: planning, implementation, observation, and reflection. The research findings showed an increase in student learning activity after the implementation of the Index Card Match learning model. Student’s activeness increased from 77.81% in the first cycle to 84.82% in the second cycle. The percentage of classical completeness also increased from 77,89% to 84.82%. These results indicate that the Index Card Match learning model is effective in fostering learning activeness among fifth-grade students and also provides an engaging and student-centered learning atmosphere that supports active involvement and understanding of lesson content.